L’accessibilité au fleuve Saint-Laurent : enjeux et perspectives pour une approche intégrée - Jean-François Bibeault (VertigO)
In Canada and Quebec, public accessibility is a major social issue in context of an integrated management perspective applied to the St. Lawrence River. Though this thematic issue make consensus in the population at least from an intentional point of view, its empirical reality is still problematic. In response, this paper clarifies multiple dimensions involved behind the concept, discuss measurement problems, and present elements of a logical framework in order to support St. Lawrence accessibility.